SCD1-Fatty Acid Desaturase Inhibitor MF-438 Alleviates Latent Inflammation Induced by Preservative-Free Prostaglandin Analog Eye Drops - Pacwa A; Machowicz J; Wojtyniak A; Pietrucha-Dutczak M; Toropainen E; Koskela A; Mrukwa-Kominek E; Lewin-Kowalik J; Smedowski A (Dove Medical Press, 2022)
Anna Pacwa,1,2 Joanna Machowicz,1 Alicja Wojtyniak,1 Marita Pietrucha-Dutczak,1 Elisa Toropainen,3,4 Ali Koskela,4 Ewa Mrukwa-Kominek,5,6 Joanna Lewin-Kowalik,1,2 Adrian Smedowski1,2,6 1Department of Physiology, Faculty of Medical Sciences in Katowice, Medical University of Silesia, Katowice, Poland; 2GlaucoTech Co, Katowice, Poland; 3School of Pharmacy, Faculty of Health Sciences, University of Eastern Finland, Kuopio, Finland; 4Department of Ophthalmology, University of Eastern Finland, Kuopio, Finland; 5Department of Ophthalmology, Faculty of Medical Sciences in Katowice, Medical University of Silesia, Katowice, Poland; 6Department of Ophthalmology, Professor K. Gibinski University Clinical Center, Medical University of Silesia, Katowice, PolandCorrespondence: Adrian SmedowskiDepartment of Physiology, Medical University of Silesia, Medykow 18, Katowice, 40-752, Poland, Tel +48 530813996, Fax +48 322525087, Email asmedowski@sum.edu.plIntroduction: Prostaglandin analogs are the first line of treatment in patients with glaucoma. Recently, many preservative-free prostaglandin analogs have been marketed to increase their tolerance in chronic use. However, potentially safer formulations have been reported to induce inflammation within ocular surface and adnexa, associated with pronounced activation of tissue macrophages.Aim: We aimed to evaluate the effect of a Stearoyl-CoA desaturase-1 (SCD1) inhibitor, MF-438, on the differentiation of monocytes exposed to eye drop detergents, representing saturated fatty acid derivatives.Methods: A culture of human peripheral blood monocytes was exposed to eye drops containing fatty acid derivatives (eye drop detergents), pf-latanoprost (Monoprost®, hydroxystearate macrogolglycerol – MGHS40) or pf-tafluprost (Taflotan®, polysorbate 80 – PS80), as well as pf-latanoprost+MF-438, MGHS40, and PS80. For the negative control C(-), monocytes were cultured in basal medium, and for the positive controls, monocytes were stimulated with Lipopolysaccharide (LPS) and Interferon γ (IFNγ) (M1 macrophages) or Interleukin-4 (IL-4) (M2 macrophages). The concentration of desaturase in the cell homogenates was determined by ELISA. The number of cells was counted under a microscope at 20x magnification.Results: The following concentrations of SCD1 (ng/mL) were measured: 7.8± 0.3 – pf-latanoprost group; 1.5± 0.4 – pf-tafluprost group; 6.8± 0.7 – MGHS40 group; 0.4± 0.002 – PS80 group; 0.9± 0.02 – pf-latanoprost+MF-438 group; 5.4± 1.6 – C(-) control; 0.5± 0.04 – M1 control; 2.2± 0.13 – M2 control. The percentages of macrophages in culture were 33.6%, 17.6%, 33%, 0%, 13.5%, 18.6%, 36.3%, and 39.3% for the pf-latanoprost, pf-tafluprost, MGHS40, PS80, pf-latanoprost+MF-438, C(-), M1, and M2 cultures, respectively. There was a strong correlation between SCD1 concentration and macrophage count in the culture (r=0.8, p< 0.05).Conclusion: Inhibition of SCD1 in monocytes prevents their transformation into macrophages after exposure to saturated fatty acid derivatives contained in eye drops, which may contribute to the limitation of latent inflammation within ocular adnexa and could possibly translate into better tolerability of the topical treatment.Keywords: prostaglandin analogs, Stearoyl-CoA desaturase-1, latent inflammation, macrophages